2020
DOI: 10.1029/2019jb018964
|View full text |Cite
|
Sign up to set email alerts
|

How Sediment Thickness Influences Subduction Dynamics and Seismicity

Abstract: It has long been recognized that sediments subducting along the megathrust influence the occurrence of giant (Mw ≥ 8.5) megathrust earthquakes. However, the limited observation span and the concurrent influence of multiple parameters on megathrust behavior prevent us from understanding how sediments affect earthquake size and frequency. Here, we address these limitations by using two‐dimensional, visco‐elasto‐plastic, seismo‐thermo‐mechanical numerical models to isolate how sediment thickness affects subductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 65 publications
3
27
0
Order By: Relevance
“…This conclusion fully supports the concept by Kelleher et al (1974) with the addition of the concept by Ruff (1989), which suggests that the key factor for a high magnitude event to occur is a large and coherent contact zone between the downgoing slab and overriding plate that could be ruptured in a single event. Note that similar results were also obtained by Herrendörfer et al (2015), Corbi et al (2017), and Brizzi et al (2020) using simplified numerical and analog modeling. This means that under the assumption that rupture length scales with rupture width, the models demonstrate that maximum magnitudes of the earthquakes are mostly controlled by the factors that increase rupture width.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This conclusion fully supports the concept by Kelleher et al (1974) with the addition of the concept by Ruff (1989), which suggests that the key factor for a high magnitude event to occur is a large and coherent contact zone between the downgoing slab and overriding plate that could be ruptured in a single event. Note that similar results were also obtained by Herrendörfer et al (2015), Corbi et al (2017), and Brizzi et al (2020) using simplified numerical and analog modeling. This means that under the assumption that rupture length scales with rupture width, the models demonstrate that maximum magnitudes of the earthquakes are mostly controlled by the factors that increase rupture width.…”
Section: Discussionsupporting
confidence: 87%
“…These are high velocity of the overriding plate forcing fast trench rollback (e.g., Christensen, 2000), mantle flow tending to flatten the slab (e.g., Ficini et al, 2017; Hager & O'Connell, 1978), and a low negative buoyancy of the slab due to its young age or incorporated oceanic plateau in combination with fast overriding by the upper plate (e.g., van Hunen et al, 2000, 2002). Recently, modeling study by Brizzi et al (2020) suggested that a decrease of the slab dip may also result from the increasing sediment thickness on the incoming plate. Note, however, that this is not a case in Central and South Andes where the dipping angles of the slabs are similar despite that the thickness of sediments is very different (Hoffmann‐Rothe et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The efforts to highlight which are the conditions enhancing the "productivity" of mega-earthquakes have recognized the potential role of several subduction-related parameters, but no consensus has been reached so far. For instance, empirical results point out at different parameters such as plates curvature (Bletery et al, 2016), roughness (e.g., van Rijsingen et al, 2019 or trench-parallel length of the subduction zone (Brizzi et al, 2018) and amount of trench sediments (Brizzi et al, 2020). Convergent margins are complex tectonic settings, whose diversity results from the interplay of several parameters operating at different spatial and temporal scales and whose relative importance is thus hard to assess (e.g., Figure 1B).…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…For example, subduction of buoyant material promotes slab flattening, while also reducing unbending as the slab enters the asthenosphere (Van Hunen et al, 2002). Brizzi et al (2020) showed that an increase in incoming sediment thickness in a subduction zone with imposed convergence velocity increases sediment accretion, trench retreat, and megathrust length, promoting large earthquakes. Increasing megathrust length may therefore offset decreasing shear stress during trench retreat.…”
Section: Discussion: Estimates Of Interface Stress and Comparison To mentioning
confidence: 99%
“…These end‐members are conceptualized as seismic and aseismic margins respectively (Heuret et al., 2011; Pacheco et al., 1993; Scholz & Campos, 1995; Uyeda & Kanamori, 1979). The controls on seismogenic behavior remain uncertain, with the leading hypotheses invoking key roles for stress state, pore‐pressure, sediment thickness, megathrust roughness or curvature, and frictional properties (Bletery et al., 2016; Brizzi et al., 2020; Pacheco et al., 1993; Scholz & Campos, 1995; Scholl et al., 2015; van Rijsingen et al., 2018; Wang & Bilek, 2011). The hypothesis that stress state influences seismogenic behavior is based primarily on experimental data (Goebel et al., 2013; Scholz, 1968) and intraplate seismicity (Schorlemmer et al., 2005; Spada et al., 2013).…”
Section: Introductionmentioning
confidence: 99%